KEBIJAKAN PENDIDIKAN PEMERINTAH HINDIA BELANDA DAN RESPON UMAT ISLAM DI JAMBI (TAHUN 1915-1942 M) - Transiska, Rizki (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2021)
Abstract: The history of education in Jambi is inseparable from Islam as a religion as well as the socio-political sutuation in Jambi at that time. Islamic educational institutions in the form of madrassas in Jambi began to exist in 1915 AD. At that time the Dutch East Indies government was in power in Jambi. To perpetuate its power, the Dutch East Indies government issued policies. One of he policies was used to suppress islamic education which was a scourge for the Dutch East Indies government. These policies include ethical politics, teacher ordonances, and wild school ordonances wich are also implemented in Jambi. This study aims to describe the implementation of colonial educational policies in jambi and the attitudes of muslims in responding to these poliecies.Abstrak: Sejarah pendidikan di Jambi tidak terlepas dari Islam sebagai agama serta situasi sosial politik di Jambi saat itu. Lembaga pendidikan Islam berupa madrasah di Jambi mulai ada pada tahun 1915 Masehi. Saat itu pemerintahan Hindia Belanda sedang berkuasa di Jambi. Untuk melanggengkan kekuasaannya, pemerintah Hindia Belanda mengeluarkan kebijakan. Salah satu kebijakannya digunakan untuk menekan pendidikan Islam yang menjadi momok bagi pemerintah Hindia Belanda. Kebijakan tersebut meliputi politik etis, tata tertib guru, dan tata tertib sekolah liar yang juga diterapkan di Jambi. Penelitian ini bertujuan untuk mendeskripsikan implementasi kebijakan pendidikan kolonial di jambi dan sikap umat Islam dalam menyikapi kebijakan tersebut.